Begonia sandsiana sp. nov. (Begoniaceae), a remarkable calciphile from the southern karst of Papua New Guinea - Takeuchi, Wayne (Phytotaxa, 2013)
Begonia sandsiana is described from previously unknown environments on the Juha limestone of Papua New Guinea's Southern Escarpment. The calciphilous species is the latest addition to Diploclinium, a section characterized (as presently understood) mainly by rhizomatous stems and male flowers with four tepals.